Slapstick comedy - Paulus, Tom; King, Rob (London : Routledge, 2010)
Introduction : restoring slapstick to the historiography of American film / Tom Paulus and Rob King -##Originality and adaptation. The good thieves : on the origins of situation comedy in the British music hall / Bryony Dixon ; D.W. Griffith shapes slapstick / Barry Salt ; Genre parody and comedic burlesque : Keystone's meta-cinematic satires / Simon Joyce ; Both sides of the camera : Roscoe "Fatty" Arbuckle's evolution at Keystone / Joanna E. Rapf ; Mud pies and tears : little Mary's funny side / Anke Brouwers -##Mechanics and modernity. Mack Sennett vs. Henry Ford / Eileen Bowser ; "Uproarious inventions" : the Keystone Film Company, modernity, and the art of the motor / Rob King ; Mechanisms of laughter : the devices of slapstick / Tom Gunning ; Slapstick skyscrapers : an architecture of attractions / Steven Jacobs ; California slapstick revisited / Charles Wolfe -##Bodies and performance. Dancing of fire and water : Charlot and L'esprit nouveau / Amy Sargeant ; Splashes of fun and beauty : Mack Sennett's bathing beauties / Hilde D'Haeyere ; Back to the "slap" : slapstick's hyperbolic gesture and the rhetoric of violence / Muriel Andrin ; The art of imitation : the originality of Charlie Chaplin and other moving-image myths / Jennifer M. Bean.
boek